Miller-Fisher Syndrome - A Case Report - Osalusi SB; Ogun SA (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2017)
Miller-Fisher syndrome is a syndrome of ataxia, areflexia and ophthalmoplegia which was first described by Miller Fisher in 1956. The disorder has an immunological basis and has been regarded as a descending form of Guillain - Barré syndrome (GBS). It is a rare clinical condition which may be confused with other common illnesses. This report describes a nine-year-old boy who presented with a five-day history of diplopia and difficulty in walking following an upper respiratory tract infection. On examination, he had ataxia, ophthalmoplegia and areflexia with cerebrospinal fluid cytoalbuminological dissociation. This case report emphasises the need to have a high index of clinical suspicion in patients with features of cranial mononeuropathy multiplex and hyporeflexia.